PALIVIZUMAB: NEW OPPORTUNITIES FOR THE ASTHMA PREVENTION? - E.A. Vishneva; L.S. Namazova-Baranova; R.M. Torshkhoeva; T.V. Kulichenko; A.Yu. Tomilova; A.A. Alekseeva; T.V. Turti (Union of pediatricians of Russia, 2011)
The steady increase in the prevalence of allergic diseases causes the social significance of this pathology. These statistics often do not reflect the true morbidity picture. The social and economic burden of allergy forces experts to seek new ways of preventing the beginnings and development of this pathology. The relationship between bronchiolitis caused by respiratory syncytial virus (RSV) infection in the early childhood and further development of asthma was proved by numerous randomized trials. The use of the drug for RSV monoclonal antibodies will reduce not only the incidence of the infection, prevent the development of bronchiolitis, but reduce the risk of asthma in early childhood.Key words: asthma, children, respiratory syncytial virus, prophylaxis.